A Semantic Wiki-based Platform for IT Service Management - Kleiner, Frank (KIT Scientific Publishing, 2015)
The book researches the use of a semantic wiki in the area of IT Service Management within the IT department of an SME. An emphasis of the book lies in the design and prototypical implementation of tools for the integration of ITSM-relevant information into the semantic wiki, as well as tools for interactions between the wiki and external programs. The result of the book is a platform for agile, semantic wiki-based ITSM for IT administration teams of SMEs.